INFLUENCE OF WEEDS ON MORPHOLOGICAL AND PHYSIOLOGICAL CHARACTERISTICS OF CORN SEEDS - SILVA, PAULO SÉRGIO LIMA E; SILVA, KATHIA MARIA BARBOSA e; MIRANDA, GLAUCO VIEIRA; RIBEIRO, MARIA CLARETE CARDOSO; GRANGEIRO, LEÍLSON COSTA (International Journal of Maize & Sorghum, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:3.0cm 3.0cm 73.7pt 3.0cm; mso-header-margin:2.0cm; mso-footer-margin:36.0pt; mso-gutter-margin:5.65pt; mso-paper-source:15 0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif]--> In family agriculture in the Brazilian Northeast, it is a common practice to plant corn seeds harvested during previous cultivations. Because weed control in those properties does not get appropriate attention, it is possible that weeds interfere with seed quality. The objective of this work was to evaluate the effects of weed control on germination, vigor (plantlet, first count and dry matter data), dimensions, and weight of corn seeds. Two experiments were carried out as a random block design with split-plots, and five replicates, either with six (AG 405 C, DKB 425, EX 6005, AG 2060, BA 8517, and BA 9513) or four (BA 9012, BA 8512, EX 4001, and EX 6004) cultivars, respectively. In both, cultivars were assigned to plots and weed control to subplots. In the first experiment, weed control was achieved by means of two hoeings. In the second, control was accomplished by two hoeings or by intercropping with cowpea (Vigna unguiculata (L.) Walp.). In both experiments, it was verified that weeds did not have an influence on germination percentage or on first count data (except for one cultivar); however, plantlet dry matter weight was higher in hand hoed plots. In those plots, width, height, and seed weight were also higher. In both experiments, the cultivars were not different in relation to germination percentage. In the first experiment, the cultivars were different with respect to first count data, while in the second experiment they were different with regard to first count and plantlet dry matter data.